ACE I/D and ACTN3 R577X polymorphisms, body composition and somatotype in top level Italian gymnasts - Massidda, M.; Toselli, S.; Brasili, P.; Calo, C. M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
ACE I/D and ACTN3 R577X polymorphisms have been associated with elite athletic status, and recently with differences in muscle strength and power, body fat and bone mineral density in human (Puthucheary et al. 2011; Yang et al. 2011). Purpose The purpose of this study was to analyze the influence of ACE I/D and ACTN3 R577X polymorphisms on body composition and somatotype of elite Italian gymnasts. Methods: Nineteen athletes of the Artistic Gymnastic Italian National Team (n=10 males, n=9 females) who were competitive at Olympic levels were genotyped for ACE I/D and ACTN3 R577X. The athletes had been gymnasts for an average of 14.3 years, and they trained for 31.2±2.5 h/week. The analysis was computed for each gender separately. Correlations were computed by mean of Pearson`s r test. Differences between genotypes and phenotypes were determined using one-way analysis of variance (ANOVA). Results: None of the tested athletes was deficient for the á-actinin-3 protein (XX genotype). In females, we found a significant negative correlation between ACTN-3 and triceps skinfold (r=-.92), and endomorphy (r=-0.83). Gymnasts carrying RR genotype showed higher values of body fat parameters than those with RX genotype (P=0.41). ACE polymorphism was significantly correlated with tight (r=.91) and triceps (r=.84) skinfolds. Athletes carrying DD genotype showed higher values of skinfolds thickness than those with ID and II genotypes (P=0.17). In males, only the R577X polymorphism displayed a significant correlation with arm (r=.74) and tight (r=.80) muscle area (TMA and AMA, respectively), mesomorphy (r=.83) and femur diameter (r=.81). Particularly, gymnasts with RR genotype showed significant higher values of AMA (RR=85.7±8.7 vs RX=72.6±9.1 cm2; P=0.04) and TMA (RR=200.2±8.7 vs RX=178.4±10.8 cm2; P=0.008), mesomorphy (RR=7.0±0.5 vs RX=5.6±0.5; P=0.002) and femur diameter (RR=9.5±0.2 vs RX=8.9 mm; P=0.02) with respect to those with RX genotype. Discussion: Our results suggested a possible effect of ACTN3 on muscle mass in males, while in female gymnasts both genes seem to have a small influence on body fat. In line with other previous researches (Massidda et al. 2009), it can be confirmed that the presence of a functional ACTN3 in fast-twitch muscle fibers might improve the potential to achieve better performance level in male and possibly female gymnasts, while ACE does not seem beneficial for gymnastic performance in both sex.